Elevating Educational Quality: A Management Strategy to Enhancing Muhammadiyah School Branding - Istikomah, Istikomah (JURNAL AL-TANZIM, 2023)
This research focuses on understanding the management carried out by Muhammadiyah schools to improve the quality of education by implementing branding strategies so that public trust becomes more robust and can benefit users of educational services. This research aims to examine the management of Muhammadiyah 1 Nganjuk Vocational School in improving the quality of education. This research uses a qualitative approach. Data collection techniques were carried out using interviews, observation, and documentation. The results of the study show that branding strategies that schools can implement to improve the quality of education include analyzing brand identity, brand personality, brand positioning, and brand communication, as well as increasing public trust by improving the quality management of school accreditation, improving school facilities and infrastructure, increasing student achievement, developing superior programs that are the hallmark of the school, creating attractive taglines that are implemented in school programs, expanding collaboration networks, increasing the selling value of the school by uploading each event on social media.